2021
DOI: 10.1039/d1gc01513c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hydrogenation of levulinic acid catalysed by spherical NHC-Ir assemblies with atmospheric pressure of hydrogen

Abstract: A practical, efficient, and mild hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL) under 1 atm H2 was realized by single-sited 3D porous self-supported N-heterocyclic carbene iridium catalyts. Quantitative yields...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…To prevent the possible deactivation of NHC–Rh complexes via cluster formation during hydrogenation, 49 we employed the “self-supporting” strategy to fabricate NHC–Rh coordination assemblies. 52 Following our recent research interests in the development of novel NHC–metal catalysts, their immobilization strategy and further applications, 52–57 we demonstrated that NHC–Rh solid coordination assemblies were efficient catalysts for the selective hydrogenation of phenols (Fig. 1d).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…To prevent the possible deactivation of NHC–Rh complexes via cluster formation during hydrogenation, 49 we employed the “self-supporting” strategy to fabricate NHC–Rh coordination assemblies. 52 Following our recent research interests in the development of novel NHC–metal catalysts, their immobilization strategy and further applications, 52–57 we demonstrated that NHC–Rh solid coordination assemblies were efficient catalysts for the selective hydrogenation of phenols (Fig. 1d).…”
mentioning
confidence: 88%
“…Recently, we have demonstrated that “self-supporting” 52–57 is an effective strategy to improve the stabilities of NHC–M complexes due to the “isolation effect”. 58 Hence, a series of solid NHC–Rh coordination assemblies 5 and 6a–d were prepared according to our previous reports.…”
mentioning
confidence: 99%
“…Although the hydrogenation of LA to GVL catalyzed by noble-metal catalysts, such as Pt, 8 Au, 9 Pd, 10 Ir, 11 and Ru 12 -based catalysts, has been extensively studied, more research efforts have been focused on non-noble metal catalysts, especially Cu-based catalysts, as listed in Table S1 † 13 . Hengne et al catalyzed LA to GVL using Cu–ZrO 2 (1 : 1) and Cu–Al 2 O 3 (1 : 1) in 2012 and obtained 100% GVL at 200 °C and 3.4 MPa pressure.…”
Section: Introductionmentioning
confidence: 99%
“…2-MeTHF also shows high energy density and poor miscibility with water, making it a promising biofuel. 5,6 The key intermediate of the conversion of LA into 2-MeTHF is GVL, which can be obtained from the hydrogenation of LA under mild conditions, [7][8][9] while the conversion of GVL into 2-MeTHF is relatively difficult due to the stability of GVL. 10 As for the reaction of GVL to 2-MeTHF, noble metal ruthenium catalysts have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%